AKTIVITAS ANTIBAKTERI AIR PERASAN DAN REBUSAN DAUN CALINCING (Oxalis corniculata L.) TERHADAP Streptococcus mutans - Ni Luh Arisa Prahastuti Winastri; Handa Muliasari; Ernin Hidayati (BERITA BIOLOGI, 2020)
Inappropriate use of antibiotics can cause bacteria to become resistant and have side effects, therefore an alternative source of antibacterial is needed. One species of plant that has antibacterial properties is calincing (Oxalis corniculata L.). Antibacterial activities of the juice and decoction of calincing leaves against Streptococcus mutans have not reported yet. This study aims to determine the antibacterial activity of the juice and decoction of calincing leaves against Streptococcus mutans. This study uses a well diffusion method with eight treatment groups, namely juice and decoction at the concentrations of 20%, 40%, 60%; listerin 100% as a positive control, and distilled water as a negative control. The diameter of the inhibitory zone of the juice and decoction of calincing leaf at a concentration of 20% are 19 mm and 24.33 mm respectively, and classified as strong growth inhibition, while the concentrations of 40% and 60% are classified as very strong growth inhibition. Growth inhibition of the juice and decoction of calincing leaf at concentration of 20% was significantly higher than the positive control. The best antibacterial activity against Streptococcus mutans is produced by the juice and decoction of calincing leaf at concentration of 60%. Increasing in the concentration of the juice or decoction of calincing leaf also increases the diameter of the inhibitory zone.